Relationship of Maternal Parenting, Exclusive Breastfeeding History, and Family Income with Nutritional Status of Toddlers Aged 2-5 Years - Rizqi Nur Halimah; Dyah Ayu Kusuma Wardani; Dewi Kusumawati (Poltekkes Kemenkes Semarang, 2026)
Background: Undernutrition occurs when energy and nutrient intake is insufficient to meet the body's requirements. Maternal parenting practices influence child growth and development through the adequacy of food intake and health status. Exclusive breastfeeding can fulfill the nutritional needs of infants up to six months of age. Family income may affect food purchasing power, which in turn influences children's food consumption. Objective: To determine the relationship between maternal parenting practices, history of exclusive breastfeeding, family income, and the nutritional status of children aged 2–5 years in Bendosari District. Methods: This was an observational study with a cross-sectional approach. A total of 57 respondents were selected using purposive sampling. Data on maternal parenting practices, history of exclusive breastfeeding, and family income were collected using questionnaires, while nutritional status was assessed using the weight-for-age (W/A) indicator. Data were analyzed using the Spearman correlation test. Results: There was a significant relationship between maternal parenting practices and the nutritional status of children under five years of age (p = 0.003; r = -0.384), indicating a weak correlation. No significant relationship was found between a history of exclusive breastfeeding and nutritional status (p = 0.092; r = 0.226), indicating a weak correlation. Likewise, no significant relationship was found between family income and nutritional status (p = 0.462; r = -0.099), indicating a very weak correlation. Conclusion: Maternal parenting practices were significantly associated with the nutritional status of children under five years of age. However, no significant relationships were found between a history of exclusive breastfeeding or family income and the nutritional status of children aged 2–5 years.